136k views
3 votes
Simplify. Show all work to receive full credit!


4(3x²y⁴)³/(2x³y⁵)⁴


1 Answer

3 votes

Answer:


(4(3x^2y^4)^3)/((2x^3y^5)^4)=(27)/(4x^6y^8)

Explanation:

Given:

The expression to simplify is given as:


(4(3x^2y^4)^3)/((2x^3y^5)^4)

First, we will simplify the numerator and denominator separately using the law of indices:


(ka^mb^n)^p=k^pa^(m* p)b^(n* p)

The numerator is simplified as:


4(3x^2y^4)^3=4(3^3x^(2* 3)y^(4* 3))=4(27x^6y^(12))

The denominator is simplified as:


(2x^3y^5)^4=2^4x^(3* 4)y^(5* 4)=16x^(12)y^(20)

Now, we divide the simplified numerator by the simplified denominator. This gives,


=(4(27x^6y^(12)))/(16x^(12)y^(20))\\=(4*27)/(16)* (x^6)/(x^(12))* (y^(12))/(y^(20))

Now, we simplify using another law of indices which is given as:


(a^m)/(a^n)=a^(m-n)


=(4*27)/(16)* (x^6)/(x^(12))* (y^(12))/(y^(20))\\=(27)/(4)* x^(6-12)* y^(12-20)\\=(27)/(4)x^(-6)y^(-8)

Now, we write the answer using only positive exponents and thus we use the given law of indices:


a^(-m)=(1)/(a^m)

Therefore, the simplified form is:


(27)/(4)x^(-6)y^(-8)=(27)/(4x^6y^8)

User Bubblez
by
4.8k points